Influence of radial shockwave on the mechanical properties of quadriceps femoris muscle fibres of a football player: case study - Łukasz Wilgocki; Małgorzata Łukowicz; Rafał Gotowski (Kazimierz Wielki University, 2018)
Radial Shockwave Therapy (RSWT) is a physical procedure often used in sports physiotherapy. Most often, the Radial Shockwave Therapy is used to loosen tight muscle strands, stimulate connective tissue, relax the fascia, treat superficial trigger points, and trigger metabolic changes in muscle fibers. The database of scientific literature lacks reports on the impact of RSWT on the muscular properties of muscles in football players. The purpose of this case report is to assess the impact of RSWT on the mechanical parameters of muscle fibres of quadriceps muscles: (Dm) - displacement of muscle, (Tc) - Time of contraction. RSWT was applied to a healthy football player on the quadriceps muscle of the thigh, finishing the lower right and left. The tensiomyography (TMG) was used to evaluate the mechanical properties of muscles fibres. The tensiomyography (TMG) was performed, followed by radial shockwave therapy (RSWT), second TMG after RSWT procedure and third TMG measurement after 5 hours from the second measurement. The tensiomyography (TMG) detected changes in the parameters of muscle work after the use of RSWT and is a useful tool to assess the impact of physical on muscle work.